Use of exercises of strong-willed gymnastics in the course of physical training of senior pupils - Кравчук, Т. М.; Чуркін, О. В. (Physical Education Theory and Methodology, 2013)
Research aim: to ground expediency of the use of exercises of volitional gymnastics in the process of P.E of senior pupils and check their efficiency. For the decision of the tasks put in-process, the next methods of research were used: analysis of pedagogical and scientifically-methodical literature; conversations are with specialists; pedagogical supervision; pedagogical testing; methods of mathematical statistics. Conclusions. Exercises of volitional gymnastics, that extraordinarily simple in mastering, do not require the presence of the specially equipped place and the implementations of various exercises based on principle without a burden, with conscious tension of corresponding muscles, can be fruitfully used in P.E of senior pupils. The use of exercises of volitional gymnastics in the process of P.E of students of higher forms assists the increase of level of development of flexibility and force, that it was experimentally well-proven during research. A most increase was observed in development of force (25%) and flexibility (24,49%) for senior pupils that executed exercises of volitional gymnastics on the lessons of physical culture and independently at home.